Herlyn-Werner-Wunderlich Syndrome: Pre-and Post-Surgical MRI and US Findings - Lopes Dias, J (2017)
Herlyn-Werner-Wunderlich syndrome (HWWS) is a rare congenital anomaly of the female urogenital tract that associates Müllerian duct anomalies with mesonephric duct anomalies. The triad of uterus didelphys, obstructed hemivagina, and ipsilateral renal agenesis characterizes this syndrome. Patients generally present with non-specific symptoms after menarche. Pelvic pain, dysmenorrhea, and palpable mass due to hematocolpos or hematometra are the most common findings. Pyohematocolpos and pyosalpinx may appear as acute complications, while endometriosis and pelvic adhesions constitute potential long-term complications. When a prenatal diagnosis of unilateral renal agenesis in newborn girls is known, a gynecological imaging study should be performed to exclude uterine and vaginal abnormalities. These patients should be followed up to ensure that a timely surgical correction is performed. The diagnosis of HWWS is difficult due to the lack of specific symptoms or findings upon physical examination. An accurate imaging description of these congenital anomalies is crucial to guide patients toward surgical treatment, relieving acute complications, and preserving the normal fertility. The authors provide a pictorial review of the magnetic resonance imaging and ultrasonography findings of the HWWS with correlation to embryological, clinical, and surgical features.